COGNITIVE PREFERENCE OF FOURTH-GRADE MIDDLE SCHOOL STUDENTS IN ARABIC GRAMMAR - Mr. Dr. Kataa Saleh Tarad (Scholars Digest Publishing, 2025)
The current research aims to measure cognitive preference of fourth-grade middle school students in Arabic grammar. To achieve this goal, the researcher chose the descriptive approach. The researcher built a cognitive preference scale tool consisting of (17) paragraphs. For each paragraph (4) patterns chosen by the student in sequence according to his cognitive preference, extracted from the topics of Arabic grammar in the Arabic language book prescribed in the curriculum, part one, amounting to (8) topics, and then the scale was presented to the specialists and experts, in Arabic language curricula and teaching methods, in order to express their observations on it, and all paragraphs of the scale were accepted and some of them were modified, and after the completion of the research tool in its final form, the researcher prepared the cognitive preference scale, and extracted the psychometric characteristics, then applied the cognitive preference scale to a sample of fourth-grade middle school students, and to identify the statistical significance of the differences, the t-test was used and the results showed that the calculated t-values were (60.47), (45.37), (43.64), and (24.59) for the patterns (remembering, principles, critical questioning, application) respectively, and they are greater than the tabular t-value, amounting to (1.96) at a degree of freedom (199) This result indicates that cognitive preference is statistically significant for all patterns, and the remembering pattern took the highest percentage, which is the first place, followed by the principles pattern, then critical questioning, then the application pattern. As for the second goal, it was found that the patterns of critical questioning, application, and principles do not have statistically significant differences, according to the gender variable, and it was found that there are statistically significant differences in the remembering pattern only in favor of females. The researcher attributed this to the fact that females have a greater cognitive preference for the remembering pattern in the desire to excel, succeed, persevere, and endure, and exert more effort. The researcher recommended providing students with cognitive preference patterns that suit their level, as it is necessary to enhance cognitive preference patterns among students through curricula, create an atmosphere for a suitable learning environment full of vitality by identifying cognitive preference patterns, and providing learners with cognitive preference patterns and identifying them to create a student who is aware of and knows what the teacher aims for in his lesson, taking into account individual differences between students in the type of study material, which reveals patterns. Cognitive preference.
Keywords: Cognitive preference - Fourth preparatory - Arabic grammar rules.